Language Planning as Nation Building Ideology, policy and implementation in the Netherlands, 1750-1850 - Rutten, Gijsbert (Advances in Historical Sociolinguistics (AHS), 2019)
The decades around 1800 constitute the seminal period of European nationalism. The linguistic corollary of this was the rise of standard language ideology, from Finland to Spain, and from Iceland to the Habsburg Empire. Amidst these international events, the case of Dutch in the Netherlands offers a unique example. After the rise of the ideology from the 1750s onwards, the new discourse of one language-one nation was swiftly transformed into concrete top-down policies aimed at the dissemination of the newly devised standard language across the entire population of the newly established Dutch nation-state. Thus, the Dutch case offers an exciting perspective on the concomitant rise of cultural nationalism, national language planning and standard language ideology. This study offers a comprehensive yet detailed analysis of these phenomena by focussing on the ideology underpinning the new language policy, the institutionalisation of this ideology in metalinguistic discourse, the implementation of the policy in education, and the effects of the policy on actual language use.